Solve differential equations via a hybrid method between homotopy analytical method and sine cosine optimization algorithm - najeeb, Mostafa raed; Qasim, Omar Saber; Entesar, Ahmed (Journal of physics. Conference series, 2021)
In this paper, ordinary differential equations (ODEs) of two types, linear and non-linear will be solved by using the homotopy analytical method (HAM), and the sine cosine algorithm (SCA) will be used to modify the parameter h and obtain a better approximate solution than what was in the previous method HAM. The suggested method, HAM-SCA, covers a solution that reveals the reliability and the efficiency correspondingly to the default method HAM by computing the maximum absolute errors (MAE) and mean square error (MSE).